Developing a risk-based inspection practices maturity model for Malaysian industries - Mohamed, Ramuna; Hassan, Che Rosmani Che; Hamid, Mahar Diana (Elsevier, 2018)
A framework was formulated based on the model of MIRM (2008) to measure the risk-based inspection (RBI) practices maturity level in the Malaysian RBI scheme users. The RBI Practices Maturity Model will assess the level of compliance and effectiveness with a recently introduced regulatory instrument for risk-based inspection practices. The developed model allowed for a ‘self-assessment’ of the maturity at RBI scheme users sites. The knowledge of the maturity level will be a point of departure to garner further improvements in RBI practices specifically and safety management system generally. Following a review of the safety culture literature, an audit instrument was designed to measure six aspects of risk-based inspection practices indicative of five levels of the RBI practices maturity. The reliability of the audit instrument was tested by applying the same question with a different approach which is selfassessment questionnaire and comparing the correlation coefficient results on each dimension between the two methods. Both correlation coefficients ranged from 0.7 to 0.9 thus demonstrating the good reliability of the measures used. The model has been found to be a practical and useful tool by RBI scheme users as a means of identifying strengths and weaknesses within the RBI practices.